THE NETWORK OF CITY PUBLIC TRANSPORT AS THE BASE FOR TRIP LENGTH DISTRIBUTION DETERMINING - Horbachov, P.; Svichynskyi, S.; Горбачев, П. Ф.; Свичинский, С. В.; Горбачов, П. Ф.; Свічинський, С. В. (Харьковский национальный автомобильно-дорожный университет, 2015)
The up-to-date methods of modelling the demand for public transport services require an objective estimation and improvement. Such an improvement can be achieved by taking into account the trip length distribution during trip matrix calculation that requires determining the reasons of regularities occurance in city population trip lengths.
СЕТЬ ГОРОДСКОГО ОБЩЕСТВЕННОГО ТРАНСПОРТА КАК ОСНОВА ДЛЯ ОПРЕДЕЛЕНИЯ ФУНКЦИИ РАССЕЛЕНИЯ НАСЕЛЕНИЯ
МЕРЕЖА МІСЬКОГО ГРОМАДСЬКОГО ТРАНСПОРТУ ЯК ОСНОВА ДЛЯ ВИЗНАЧЕННЯ ФУНКЦІЇ РОЗСЕЛЕННЯ НАСЕЛЕННЯ
Keywords: trip length distribution; distribution law; stop co-ordinate; distance between stops; trip matrix; функция расселения; закон распределения; координаты остановок; расстояние между остановками; матрица корреспонденций; функція розселення; закон розподілу; координати зупинок; відстань між зупинками; матриця кореспонденцій; 656.072